Pengaruh Personal Branding Nasywa Rahmah di Instagram @Awlapar terhadap Minat Kuliner di Kota Padang - Azizah, Frecya Yoli; Nugroho, David Rizar; Yuliasari, Ika (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study is motivated by self-image which is an important strategy for content creators in building an image on social media. Nasywa Rahmah is one of the culinary content creators who has succeeded in attracting the attention of the audience through her content. This study aims to analyze the influence of Nasywa Rahmah's personal branding on the culinary interests of people in Padang City. This study uses a quantitative method with an explanatory approach. Data were obtained through an online questionnaire with a purposive sampling technique involving 125 respondents who were followers of the @awlapar account. The independent variable in this study is self-image with three main indicators: characteristics, relevance, and consistency, while the dependent variable is culinary interest, measured using the AIDA model. This study uses data analysis carried out by simple linear regression using SPSS software. The results of the study showed that Nasywa Rahmah's personal branding influenced the culinary interests of the people of Padang City, which showed that Nasywa Rahmah's self-image was in the high category, and the respondents' culinary interests were also high. The results of the simple linear regression test showed that the three personal branding variables had a significant effect on culinary interests, both simultaneously and partially. The relevance variable gives the most dominant contribution to increasing culinary interest, indicating that strong and consistent personal branding can influence consumer preferences and behavior in choosing a place to eat. Thus, self-image through social media has great potential in supporting local culinary promotion.